THE EFFECT OF DEBT TO EQUITY RATIO, RETURN ON ASSET, AND PRICE EARNING RATIO ON STOCK RETURNS IN CIGARETTE SUB-SECTOR MANUFACTURING COMPANIES LISTED ON THE IDX FOR THE PERIOD 2012-2022 - Intan Ainur Rohmah; Sri Nuringwahyu; Eny Widayawati (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2024)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Return On Asset (ROA), and Price Earning Ratio (PER) on stock returns, both partially and simultaneously. The research method used is quantitative with purposive sampling technique on 44 samples, analyzed using multiple linear regression with SPSS 23 software. The results showed that DER (X1) had no significant effect on stock returns (t value < t table (-0.983 > 1.684) and sig value. > 0.05 (0.555 > 0.05)), which indicates that investors focus more on other factors such as earnings stability, dividend policy, and general financial performance rather than the company's debt structure. ROA (X2) has a positive and significant effect on stock returns (t value > t table (2.540 > 1.684) and sig value. < 0.05 (0.015 < 0.05)), reflecting the operational efficiency and the company's ability to generate profits from its assets. PER has a positive and significant effect on stock returns (t value> t table (2.095> 1.684) and sig value. < 0.05 (0.043 < 0.05)), reflecting positive market expectations of future earnings growth. Simultaneously, DER, ROA, and PER have a significant effect on stock returns with the test value of F count> F table (2,840> 2,839) and sig value. <0.05 (0.050 <0.05), with a contribution of 11,4% to the dependent variable.